Mengungkap Implementasi Konsep Gelah Druwen Pengelolaan Keuangan Desa Adat Jumpai - Ni Komang Suwini; Anantawikrama Tungga Atmadja (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the source of funds for gelah druwen in adat Jumpai village, and to find out the implementation of the gelah druwen concept of financial management in adat Jumpai village. This research with a qualitative method using primary data sources in the form of interviews with bendesa/chairman, petajuh/vice chairman, petengen/treasurer, penyarikan/secretary, prajuru and the people of the Adat Jumpai village. The results of this study indicate that the source of found for gelah druwen in adat Jumpai village comes from 1) paturunan krama village, 2) punia funds, 3) saving interest, 4) immigrants, 5) banjar/furniture rental income along with stall/kiosk contracts. The role for financial management of the adat Jumpai vilage is able to realize transparency, matual trust and integration between prajuru, kelihan, and the people of the adat Jumpai village.